Konstruksi Ilmu Dan Metodologi Pengetahuan Di Barat Serta Pengaruhnya Dalam Pendidikan Islam Di Indonesia - Hidayat, Rahmat; Rijal , Syamsul (Jumper: Journal of Educational Multidisciplinary Research, 2024)
The term knowledge which means knowledge. The term knowledge also contains the meaning of expertise and skills that humans obtain through experience and education. Critical study of western epistemology is not something that is considered new. There have been many studies in the form of research, book writing journals that attempt to correct, analyze and find several weaknesses that exist in western epistemology. This criticism not only emerged from among Muslims who referred to Islamic values, but also criticism from western intellectual circles themselves. Islamic education is an effort to develop, encourage and invite people to progress further based on high values ​​and a noble life, so that a more perfect person is formed, both in relation to reason, feelings and actions. Islamic epistemology in the form of the Qur’an and Hadith, Reason and Heart, and the Senses. Therefore, epistemology also has an important role in the world of education as a tool for realizing the truth of science in the world of human education. Thus, it is hoped that Islamic education is not just a transfer of religious knowledge, but should be able to direct and shape behavior in accordance with religious guidance.